1997
DOI: 10.1046/j.1365-2249.1997.4361335.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular aberrations in the MHC class I-restricted pathway for antigen presentation in methylcholanthrene sarcomas from nude mice: discrepancies between MHC mRNA and surface protein

Abstract: SUMMARYIn a previous study, we demonstrated that eight sarcomas induced by chemical carcinogenesis in nude mice were rejected by syngeneic immunocompetent recipients at a much higher rate than eight sarcomas induced with the same method in syngeneic immmunocompetent mice. In the present study, we investigated these 16 sarcomas for structural and quantitative aberrations in components of the MHC class I-restricted antigen-processing and -presentation pathway. Considerable discrepancies between mRNA levels and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 49 publications
1
4
0
Order By: Relevance
“…Consequently, we speculate that the poor expression of HLA molecules on SARC-L1 cells allow them to escape from adaptive immunity. Interestingly HLA-A2 expression on SARC-L1 was increased after IFN-γ exposure, suggesting a quantitative abnormality of the HLA class I pathways as previously described in sarcoma [ 26 , 27 ]. This overexpression of HLA-A2 could favor the recognition of SARC-L1 by CD8 + TILs cells within the tumor bed.…”
Section: Discussionsupporting
confidence: 62%
“…Consequently, we speculate that the poor expression of HLA molecules on SARC-L1 cells allow them to escape from adaptive immunity. Interestingly HLA-A2 expression on SARC-L1 was increased after IFN-γ exposure, suggesting a quantitative abnormality of the HLA class I pathways as previously described in sarcoma [ 26 , 27 ]. This overexpression of HLA-A2 could favor the recognition of SARC-L1 by CD8 + TILs cells within the tumor bed.…”
Section: Discussionsupporting
confidence: 62%
“…The function of TAP molecules in the tumour lines has been tested in an indirect manner, as empty class I molecules are known to be expressed on the cell surface in increased amounts when TAP‐deficient cell lines are cultured at reduced temperature [31]. None of the tumour lines increased their MHC class I surface expression at low temperature [29]. We therefore conclude that there is no functional defect of TAP in our tumour cell lines.…”
Section: Discussionmentioning
confidence: 89%
“…Of these the best understood is the accumulation of defects in the TAP molecules in human cervical carcinoma cells [22]. A thorough investigation of the present panel of MCA sarcomas has not revealed low MHC expression, structural defects in the MHC class I molecules [29], or lack of sensitivity to IFN‐ γ [30]. The MCA tumours used here have also been investigated for structural defects in both the proteasome complex and the heat shock proteins, and for changes in ICAM‐1 expression, but no defects were detected [29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is striking that these five tumour lines all originated from tumours induced in immunodeficient mice, while the six tumour cell lines expressing the highest levels of MHC class I after IFN-g treatment all except for one originated from immunocompetent mice, but an explanation to this has not been found. It may be important to notice that nearly all of the tumours from nude mice studied previously had severe discrepancies between levels of mRNA for MHC class I and cell surface proteins, indicating an abnormal gene regulation, while the large majority of tumours from nu/þ mice had concordant levels of mRNA and surface protein [47]. Examination of these high-and low-responding tumour lines by flow cytometry showed that they all expressed low but equal amounts of IFNreceptor on the surface.…”
Section: Discussionmentioning
confidence: 95%